The Contribution of Entrepreneurial Knowledge and Self-Confidence to Youth Entrepreneurial Interests at the Orphanage and Its Implications Counseling Services - Rezlan Sindala; Megaiswari Biran Asnah (International Journal of Applied Counseling and Social Sciences, 2022)
One of the roles of orphanage institutions is to foster an interest in entrepreneurship in adolescents in orphanages, so that orphanage children can become independent entrepreneurs after graduating from the orphanage. The knowledge possessed by individuals determines entrepreneurial interest. In addition, the interest in entrepreneurship is also determined by self-confidence. This research aims to (1) describe the contribution of entrepreneurial knowledge, self-confidence and the interest in entrepreneurship in orphanage youth, (2) examine the contribution of entrepreneurial knowledge to the interest in entrepreneurship in orphanage youth, (3) examine the contribution of self-confidence to the interest in entrepreneurship in orphanage youth, and (4) analyze entrepreneurial knowledge and self-confidence together on the interest in entrepreneurship for orphanage youth. This research uses a quantitative approach with a descriptive correlational method. The population of this study were all adolescents from the Budi Luhur Orphanage with an age range of 15 to 18 years, totalling 86 people, using a total sampling technique. This research instrument uses a Likert scale model about the contribution of entrepreneurial knowledge, self-confidence conformity and entrepreneurial interest in orphanage youth. Data were analyzed using descriptive statistical techniques, then simple linear and multiple linear regression analyses. The research findings show that, in general, the entrepreneurial knowledge of the Orphanage youth is in the high category, the self-confidence of the Orphanage youth is in the high category, and the interest in entrepreneurship of the Budi Luhur Orphanage youth is in the very high category. There is a solid and positive relationship between entrepreneurial knowledge and self-confidence with interest in youth entrepreneurship at the Budi Luhur Takengon Orphanage. This research has implications as the level of interest in entrepreneurship is influenced by entrepreneurial knowledge and self-confidence, both of which represent external and internal factors.